Prevalence and Effects of Emphysema in Never-Smokers with Rheumatoid Arthritis Interstitial Lung Disease - Joseph Jacob; Jin Woo Song; Hee-Young Yoon; Gary Cross; Joseph Barnett; Wen Ling Woo; Fern Adams; Maria Kokosi; Anand Devaraj; Elisabetta Renzoni; Toby M. Maher; Dong Soon Kim; et al. (EBioMedicine, 2018)
Aims: Autoimmune conditions such as rheumatoid arthritis-related interstitial lung disease (RA-ILD) have been linked to the existence of emphysema in never-smokers. We aimed to quantify emphysema prevalence in RA-ILD never-smokers and investigate whether combined pulmonary fibrosis and emphysema (CPFE) results in a worsened prognosis independent of baseline disease extent. Methods: RA-ILD patients presenting to the Royal Brompton Hospital (n = 90) and Asan Medical Center (n = 155) had CT's evaluated for a definite usual interstitial pneumonia (UIP) pattern, and visual extents of emphysema and ILD. Results: Emphysema, identified in 31/116 (27%) RA-ILD never-smokers, was associated with obstructive functional indices and conformed to a CPFE phenotype: disproportionate reduction in gas transfer (DLco), relative preservation of lung volumes. Using multivariate logistic regression, adjusted for patient age, gender and ILD extent, emphysema presence independently associated with a CT-UIP pattern in never-smokers (0.009) and smokers (0.02). On multivariate Cox analysis, following adjustment for patient age, gender, DLco, and a CT-UIP pattern, emphysema presence (representing the CPFE phenotype) independently associated with mortality in never-smokers (p = 0.04) and smokers (p < 0.05). Conclusion: 27% of RA-ILD never-smokers demonstrate emphysema on CT. Emphysema presence in never-smokers independently associates with a definite CT-UIP pattern and a worsened outcome following adjustment for baseline disease severity.